Managing labour migration in Europe ideas, knowledge and policy change - Balch, Alex.; ebrary, Inc. (Manchester, U.K. ; New York : Manchester University Press ; New York : Distributed in the U.S. by Palgrave Macmillan, 2010)
Labour migration has become one of the hot topics in Europe, especially since 2000 with the shift from restriction to managed migration. This book provides an authoritative account of policy change over labour migration in Europe during this new era of governance.
Includes bibliographical references (p. [205]-226) and index.
Electronic reproduction.
Keywords: Foreign workers -- Europe; Foreign workers -- Government policy -- Europe; Electronic books